Counting the hills : assessing development in Chittagong Hill Tracts - Rafi, Mohammad; Chowdhury, A. M. Raza. (Dhaka : University Press, 2001)
Research report on the social, economic, demographic and environmental aspects of Chittagong Hill Tracts region; contributed articles.
Includes bibliographical references (p. [251]-256) and index.
Keywords: Community development -- Bangladesh -- Chittagong Hill Tracts (Region); Rural development -- Bangladesh -- Chittagong Hill Tracts (Region); Sustainable development -- Bangladesh -- Chittagong Hill Tracts (Region)